First record of leucism in the volcano rabbit (Romerolagus diazi), endemic to México - Guerrero, José Antonio; Montes-Carreto, Leslie M.; Uriostegui-Velarde, Juan Manuel; Brigada Comunitaria Teporingos 1 (Therya Notes, 2022)
Leucism is the total or partial loss of the pigmentation of the fur or plumage without affecting the color of the eyes, skin, and nails. During one of the daily surveillance and protection tours carried out by the Teporingos 1 community brigade, a leucistic juvenile zacatuche was recorded within the San Miguel Topilejo Community Ecological Reserve of México City, México. This note reports the first record of leucism in Romerolagus diazi and discusses the relevance of this finding.